Strategi Mitigasi Dampak Kejadian Banjir di Kecamatan Rumbai Pesisir Kota Pekanbaru - Yasir Prayuna; Mubarak Mubarak; Imam Suprayogi (Jurnal Zona, 2023)
Rumbai pesisir is one of the districts that is often affected by flooding in the city of Pekanbaru. This research was carried out to formulate mitigation strategies from ecological, social, and economic perspectives to minimize the impacts of floods in the Rumbai sub-district of Pekanbaru City. The data obtained from questionnaires, interviews, direct field observations, and also literature reviews are analyzed descriptively and plotted into a SWOT diagram. From the ecological perspective, Pekanbaru has a medium to high category of rainfall with a high frequency of flood. Many of the drainage channels in Sri Meranti area are unmaintained and clogged. The social conditions show that the majority of Sri Meranti population have productive age and intermediate education so that they can be more educated in terms of mitigation. The economic conditions show that there is a low-income level of the Sri Meranti population which is below the UMK. Of Pekanbaru. Government contributions in handling floods are needed but the budget is insufficient. The resulting strategy in mitigating the flood impact in Rumbai is the S-O (Strength-Opportunities) strategy which supports an aggressive strategy in taking advantage of all the strengths and opportunities that exist.